Upaya Meningkatkan Motivasi Belajar Dengan Menggunakan Quizizz Paper Mode Kelas V Di SDN 16 Mataram Tahun Ajaran 2022/2023 - Jannah, Miftahul; Mahardikha, Deni Tri Agus; Istiningsih, Siti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
The purpose of this study is to determine the effect of using quiz mode on the learning motivation of students of V SDN 16 Mataram, a total of 27 students. This type of inquiry is a collaborative classroom inquiry. The data collection methods used in this study were observation, questionnaire and documentation. The results of the study showed that there was an increase in students’ motivation to learn, and then in student learning outcomes, as can be seen from the results of pre-course training: 55% with the “Satisfactory” (C) category, the first cycle was in the “Good” (B) category. , and in the second cycle there was an increase to 81% of the “Very Good” (SB) category. Thus, it can be concluded that through the use of quiz mode, it is possible to increase the motivational learning abilities of students of class V SDN 16 Mataram.